2019
DOI: 10.22159/ijap.2019.v11s6.33575
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D, Vitamin D Receptor Gene Foki Polymorphism, and Cathelicidin in Tuberculosis Infection in Children

Abstract: Objective: Recent studies have reported that vitamin D has an important role in tuberculosis. Polymorphism of single nucleotide polymorphism (SNP) rs2228570 or FokI will generate proteins with various amino acid lengths, and affect the molecular physiological roles of vitamin D. Cathelicidin acts as an antimicrobial directly against Mycobacterium tuberculosis (Mtb) and mediator autophagy by macrophages induced by vitamin D. This study aims to determine the role of vitamin D, vitamin D receptor gene SNP rs22285… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…1 Cathelicidin, interferon gamma (IFN-γ), and toll-like receptors (TLR) are significant mediators of the inflammatory response against M. tuberculosis. 7,8 At the level of the macrophage, which is involved in cathelicidin and interferon gamma (IFN-γ) mediated activity against mycobacteria, calcitriol affects the pathogenesis of M. tuberculosis infection or illness. 7 There are temporal changes in immunity throughout pregnancy, and pregnant women have a unique immunological profile compared to non-pregnant adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Cathelicidin, interferon gamma (IFN-γ), and toll-like receptors (TLR) are significant mediators of the inflammatory response against M. tuberculosis. 7,8 At the level of the macrophage, which is involved in cathelicidin and interferon gamma (IFN-γ) mediated activity against mycobacteria, calcitriol affects the pathogenesis of M. tuberculosis infection or illness. 7 There are temporal changes in immunity throughout pregnancy, and pregnant women have a unique immunological profile compared to non-pregnant adults.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by a meta-analysis study that reported low calcitriol in pregnant women will increase the risk of tuberculosis infection in children and calcitriol deficiency. 7,8 In this work, we investigated the relationship between calcitriol levels in LTBI pregnant women and calcitriol levels in their newborns as well as the relationship between cathelicidin, TLR2, and IFN-levels in the newborns. We also examined the effects of cathelicidin and IFN-γ levels in LTBI pregnant women on the cathelicidin and IFN-γ levels of their neonates in order to ensure that both the children and mothers with LTBI have an adequate immune system to preventative TB activity.…”
Section: Introductionmentioning
confidence: 99%